ANALYSIS OF FEATURES BUILT HOUSING KHARKIV AND ARCHITECTURAL DESIGN SOLUTIONS ITS RECONSTRUCTION - and (Municipal economy of cities. Series: «Economy science», 2013)
The scientific-applied of perfection of methodology of choice of effective variant of reconstruction of dwelling buildings. The analysis of features of settlements of city Kharkov is made and methods of reconstruction buildings are considered.